EFEKTIVITAS PERATURAN BUPATI NOMOR 18 TAHUN 2011 TENTANG KETENTUAN WAJIB SHALAT BERJAMAAH BAGI PEGAWAI DI LINGKUNGAN PEMKAB ROKAN HULU - Afridilla, Rizki; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Of the obligation to pray, Rokan Hulu Regent Regent pour in Regulation No. 18 of 2011 on Liability For Employee Muslim prayer to pray at Noon and Asr prayer at the Grand Mosque Sand Pengaraian. Obligations noon prayer and Asr prayer only reserved for employees with offices around the neighborhood Islamic Center Mosque. Liabilities pray together that began since 25 april 2011 was conducted simultaneously in the district government Rokan Hulu. This event led by the regent and his deputy. Regent issued a transport allowance cuts for employees three consecutive times - also for one month is not praying in congregation.To analyze these problems the author uses the theory Shaun Tyson and Tony Jackson which is consistent with the theory that problem. This research is a descriptive qualitative approach, where data collection technique is the technique of observation and interviews with key informants as key informants.To can be concluded that in order to achieve the effectiveness of the decree No. 18 of 2011 on Mandatory Provisions prayer congregation Environment For Employees in Rokan Hulu regency responsible employees are required to perform the duties of prayer in congregation, the responsibility is accompanied by a full awareness of civil servants prayers in congregation in the absence coercion and fear of sanction given by the leadershipKeywords: Effectiveness, the decree No. 18 of 2011, Obligatory Prayer congregation